Tricoscopy findings in tinea capitis. A rapid method of diagnosis. - Elghblawi, E. (European Journal of Pediatric Dermatology, 2016)
Dermoscopy is a method of growing significance in the diagnosis of dermatological pigmented skin diseases. Here was described a young boy with tinea capitis and multiple “comma hairs” and “zigzag hairs” on dermoscopy examination. The latter finding can be useful for the diagnosis.